Antithrombotic therapy and cardiovascular outcomes after transcatheter aortic valve implantation in patients without indications for chronic oral anticoagulation: a systematic review and network meta-analysis of randomized controlled trials. Issue 3 (14th January 2023) - Guedeney, Paul; Roule, Vincent; Mesnier, Jules; Chapelle, Celine; Portal, Jean-Jacques; Laporte, Silvy; Ollier, Edouard; Zeitouni, Michel; Kerneis, Mathieu; Procopi, Niki; Barthelemy, Olivier; Sorrentino, Sabato; et al.
Abstract: Aims: As the antithrombotic regimen that may best prevent ischaemic complications along with the lowest bleeding risk offset following transcatheter aortic valve implantation (TAVI) remains unclear, we aimed to compare the safety and efficacy of antithrombotic regimens in patients without having an indication for chronic oral anticoagulation. Methods and results: We conducted a PROSPERO-registered (CRD42021247924) systematic review and network meta-analysis of randomized controlled trials evaluating post-TAVI antithrombotic regimens up to April 2022. We estimated the relative risk (RR) and 95% confidence intervals (95% CIs) using a random-effects model in a frequentist pairwise and network metanalytic approach. We included seven studies comprising 4006 patients with a mean weighted follow-up of 12.9 months. Risk of all-cause death was significantly reduced with dual antiplatelet therapy (DAPT) compared with low-dose rivaroxaban + 3-month single antiplatelet therapy (SAPT) (RR 0.60, 95% CI 0.41–0.88), while no significant reduction was observed with SAPT vs. DAPT (RR 1.02, 95% CI 0.67–1.58) and SAPT and DAPT compared with apixaban or edoxaban (RR 0.60, 95% CI 0.32–1.14 and RR 0.59, 95% CI 0.34–1.02, respectively). SAPT was associated with a significant reduction of life-threatening, disabling, or major bleeding compared with DAPT (RR 0.45, 95% CI 0.29–0.70), apixaban or edoxaban alone (RR 0.45, 95% CI 0.25–0.79), and low-dose rivaroxaban + 3-month SAPT (RR 0.30, 95% CI 0.16–0.57). There were no differences between the various regimens with respect to myocardial infarction, stroke, or systemic embolism. Conclusion: Following TAVI in patients without an indication for chronic oral anticoagulant, SAPT more than halved the risk of bleeding compared with DAPT and direct oral anticoagulant-based regimens without significant ischaemic offset. Graphical Abstract: